2021
DOI: 10.1111/jzs.12563
|View full text |Cite
|
Sign up to set email alerts
|

Introgressive hybridization between two phylogenetic lineages of charrs ( Salvelinus : Salmonidae) in northeastern Asia

Abstract: Many lacustrine charrs of the genus Salvelinus were described as separate species, and their origin and phylogenetic relationships are still under debate. In this study, we described the genetic variation of charrs from Lake Grand (Elikchan Lake Group, the mainland coast of the Sea of Okhotsk, Russia) and several locations outside of this system based on eight microsatellite (ms) loci and mitochondrial (mt) DNA control region. We tested the hypothesis of the resident charr membership to (a) the Arctic lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Longer DNA sequences have previously been proven to give an acceptable resolution of relatively high connections in fish [ 317 ]. A study by Oleinik et al (2021) additionally showed that mitogenomes could make up a reliable phylogenetic tree and resolve relationships between closely related species of loaches [ 318 ]. On the basis of morphological similarity, the boganids of Chukotka and Taimyr were attributed to the same species [ 286 , 306 ].…”
Section: Phylogenetic Characteristics Of Salmonmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer DNA sequences have previously been proven to give an acceptable resolution of relatively high connections in fish [ 317 ]. A study by Oleinik et al (2021) additionally showed that mitogenomes could make up a reliable phylogenetic tree and resolve relationships between closely related species of loaches [ 318 ]. On the basis of morphological similarity, the boganids of Chukotka and Taimyr were attributed to the same species [ 286 , 306 ].…”
Section: Phylogenetic Characteristics Of Salmonmentioning
confidence: 99%
“…An earlier study showed S. alpinus individuals with introgressed haplotypes from the Bering clade of S. malma along the eastern coast of Siberia to be parapatric [ 171 ]. In a very recent study, mtDNA introgression from S. malma malma to S. taranetzi near the Sea of Okhotsk, due to which representatives of the first species did not remain in this location completely [ 318 ]. In addition, postglacial hybridization between different glacial lineages of S. alpinus has been demonstrated to survive in separate refugia [ 170 ].…”
Section: Phylogenetic Characteristics Of Salmonmentioning
confidence: 99%